The behavior of Projectile Ricochet off various wooden targets - Mohd Shukry, Abdul Majid; Birch, Robert S.; M.I. Jais; Mohd Noor Arib, Md Rejab; Hafizawati, Zakaria (Kolej Universiti Kejuruteraan Utara Malaysia, 2008)
Link to publisher's homepage at http://jere.unimap.edu.my